Sandra M. Gilbert and Susan Gubar's The Madwoman in the Attic : The Woman Writer and the Nineteenth-Century Literary Imagination /: The Woman Writer and the Nineteenth-Century Literary Imagination. (2018) - Pohl, Rebecca
No abstract available